1990
DOI: 10.1159/000213220
|View full text |Cite
|
Sign up to set email alerts
|

Urinary IgG and IgA Antibodies in Elderly Individuals with Bacteriuria

Abstract: We studied the urinary IgG and IgA antibody in elderly subjects without bacteriuria, with asymptomatic bacteriuria and symptomatic urinary infection. Elderly individuals with asymptomatic bacteriuria had significantly elevated antibody levels relative to controls. When followed up to 12 months with persistent bacteriuria, antibody levels tended to persist but were variable. In elderly women with elevated urinary antibody titers, site of infection tended to be localized to the kidney, but antibody levels within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 9 publications
(16 reference statements)
0
15
0
Order By: Relevance
“…Antibody developed to these antigens is widely cross‐reactive among the Enterobacteriaceae, the most common infecting organisms in the institutionalized bacteriuric elderly. The antibody level correlates with urinary antibody measured to the whole cell 14 . Thus, the antibody may potentially be used, as we have done in this study, as an assay to identify elderly bacteriuric subjects with a more vigorous local response to their infection.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Antibody developed to these antigens is widely cross‐reactive among the Enterobacteriaceae, the most common infecting organisms in the institutionalized bacteriuric elderly. The antibody level correlates with urinary antibody measured to the whole cell 14 . Thus, the antibody may potentially be used, as we have done in this study, as an assay to identify elderly bacteriuric subjects with a more vigorous local response to their infection.…”
Section: Discussionmentioning
confidence: 63%
“…Renal failure, however, occurred no more frequently in the elevated than normal antibody group. In addition, an earlier study has shown that while elderly asymptomatic bacteriuric women with elevated urinary antibody are likely to have renal infection, as localized by the Fairley bladder washout technique, only 50% of women with renal infection have elevated antibody levels 14 . Elevated urinary antibody in response to persistent bacteriuria may identify the elderly individual who has “aged” further immunologically or with greater immune dysregulation due to associated chronic diseases, 22 resulting in an inappropriate local immune and inflammatory response with detrimental effects to the host over prolonged time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations